The conduct of summary trial in military law - practice and procedure / Amir Hamzah Ahmad, Kamarularifin Nordin and Mohd Nasir Abd Aziz - Ahmad, Amir Hamzah; Nordin, Kamarularifin; Abd Aziz, Mohd Nasir (2005)
The Armed Forces of Malaysia is a well-known organisation that has a quality of discipline differs from other organisation. This is because army personnel not only subject to the civil laws which are in force in the Federation, but they are also subject to the Armed Forces Act (AFA) 1972 (the legislation that is applicable only to the members of the Armed Forces). Under Section 95 of AFA 1972, a COs is given wide powers to try personnel under his command. This trial is known as summary trial. The spirit behind the Act is to confer such powers to a COs which is not only to maintain discipline but also to make sure that the administration of personnel can be executed fluently. Apart from that, it is also to increase respect among the personnel in the unit to their COs as well as to the rule and regulation provided under the Act. In this era of globalisation, the army personnel are well educated. They are in fact have a little bit of knowledge with regard to their fundamentals right under the law. As a result, there are few cases where the decision of COs in summary trials have been revoked or revised by the higher authority due to breach of rules and procedures provided under the Act. In addition, the procedures that govern summary trial is seen to be abuse by a COs. This is because a COs during the summary trial acts as judge and prosecutor to the accused. This situation could raised the possibilities of breach of rules of Natural Justice principally Rules Against Bias. Therefore, the main purpose of this paper is to explore the practice and procedure of summary trial conducted by a COs. How far this practice and procedures is consistent with the rules of Natural Justice principally Rules Against Bias is yet to be discovered.